A Retroperitoneal Isolated Enteric Duplication Cyst Mimicking a Teratoma: A Case Report and Literature Review. (19th December 2016) - Momosaka, Daichi; Ushijima, Yasuhiro; Nishie, Akihiro; Asayama, Yoshiki; Ishigami, Kousei; Takayama, Yukihisa; Okamoto, Daisuke; Fujita, Nobuhiro; Ikeda, Tetsuo; Uchida, Keiichiro; Sugimoto, Masaaki; Kohashi, Kenichi; et al.
Abstract : Enteric duplication cysts lacking anatomic association with the gastrointestinal tract are called isolated enteric duplication cysts (IEDCs). We present an atypical case of a retroperitoneal IEDC with a tortuous tubular complex shape that enfolded the surrounding retroperitoneal fat and mimicked a retroperitoneal teratoma. Multiplanar reconstruction images should be used to evaluate such a lesion correctly. A tortuous tubular complex shape could be a key finding to differentiate from other retroperitoneal cysts.